1994
DOI: 10.1002/ar.1092390203
|View full text |Cite
|
Sign up to set email alerts
|

Extractions reveal specific argentophilic proteins in rat and bull sperm heads

Abstract: Reduction in the number of argentophilic proteins appears to be involved in a series of changes in the cyto-architecture of developing spermatids. Tentative cytoskeletal nature of argentophilic proteins remains to be identified. Nevertheless, they may have important physical relations with the higher-order organization of the sperm head cytoskeleton and overlying membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Regional distribution of actin in the perinuclear theca resembles that of calicin, a highly extraction resistant basic protein specific for the a b sperm head cytoskeleton, including the murine perforatorium (Longo et al, 1987;Paranko et al, 1988). Actin may also colocalize with a group of less well identified argentophilic constituents of the cytoplasm (Yagi and Paranko, 1994). Indeed, based on the specific distribution and apparent conformation to a three-dimensional packing of the perinuclear theca, these accumulations of proteins may play a structural role in maintaining the integrity of the sperm head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional distribution of actin in the perinuclear theca resembles that of calicin, a highly extraction resistant basic protein specific for the a b sperm head cytoskeleton, including the murine perforatorium (Longo et al, 1987;Paranko et al, 1988). Actin may also colocalize with a group of less well identified argentophilic constituents of the cytoplasm (Yagi and Paranko, 1994). Indeed, based on the specific distribution and apparent conformation to a three-dimensional packing of the perinuclear theca, these accumulations of proteins may play a structural role in maintaining the integrity of the sperm head.…”
Section: Discussionmentioning
confidence: 99%
“…On this background and in view of the present findings it is tempting to propose that the negative immunocytochemical results in the rat and mouse spermatozoa are, within limits of the antibody specificity, due to the structural masking of the antigens. In this regard, it is significant to note that anionic SDS which specifically dissolves the plasma and acrosomal membranes and some of the fibro-granular material of the perinuclear theca (O'Brien and Bellve, 1980;Bellve et al, 1990Bellve et al, , 1992Yagi and Paranko, 1994) does not only retain actin in the perinuclear theca but also effectively demasks cryptic actin epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…A rigid postacrosomal sheath is a putative site for actin in a number of mammalian spermatozoa (Clarke and Yanagimachi, 1978;Tamblyn, 1980;Clarke et al, 1982;Flaherty et al, 1986Flaherty et al, , 1988Yagi and Paranko, 1992), where it may interact with actin-binding proteins such as spectrin (Kann et al, 1993) and a group of basic proteins including calicin and multiple band proteins (Longo et al, 1987;Paranko et al, 19881, and with less well identified silver binding proteins (Yagi and Paranko, 1994).…”
Section: Lmmunolocalization Ofmentioning
confidence: 99%
“…SDS is a stronger detergent than Triton X-100, which can destroy the nucleus, so that it has additional property that melt the acrosomal membrane, if exceeded the optimum value, and finally makes disappear [19][20][21]. However, application of 0.05% SDS successfully separates the spermatid head-tail connection.…”
Section: Discussionmentioning
confidence: 99%